Cross-protection conferred by live-attenuated Salmonella Enteritidis vaccine against S. Heidelberg and S. Infantis - Joaquim, Patricia Estefania; Balbiani, Facundo; Socas, Maria Laura; Arenas Mosquera, David José; Sara, Lucas; Sarabia, Jaime; Paulet, Pascal; Sesti, Luiz; Chacana, Pablo (American Association of Avian Pathologists, 2024)
Poster